Relational Aggression of Elementary School Students Based on Gender - Firmansyah, Ahmad; Erwinda, Lira (Bulletin of Counseling and Psychotherapy, 2024)
Identifying gender differences in relational aggression (RA) is critical, given its profound impact on students' social dynamics and psychological well-being, as well as the need to develop more focused and effective prevention and intervention strategies in educational settings. This study aims to analyze the patterns and characteristics of relational aggression among 11-year-old elementary school students, with a focus on identifying any significant differences or trends based on gender. The type of research used is comparative research. The sample in this study was 457 respondents consisting of 19.3% male and 80.7% female. The Relational Aggression Scale was used to collect data on the relational aggression of elementary school students in various elementary schools in Banten province. The data collection process was facilitated by the teachers in each participating school. The analysis technique used was descriptive and a different test with the Welch test. The results showed that there was a significant difference in the relational aggression of boys and girls, with an average score difference of -0.37 logit between boys and girls.